The Contradiction of Agile Measures: Customer as Focus, but Process as Measured? - Storti, A; Clear, Tony (Association for Information Systems (ACIS), 2020)
Performance measures are being used in the agile approach as a powerful tool to understand the customer's impact of a software delivery. However, it is common to find measures related to the process instead of the customer, which would cause the team to forget the customer value delivery. This research study adopts a systematic mapping process to understand which agile approach is related to performance measures, what kind of measures are being used, and if the papers are focused on product measures or process measures. The analyzed articles showed that Scrum is the most frequently referenced agile approach that mentions measures. However, the review shows that the focus was on process measurements, while, despite the rhetoric about customer focus and agility, product measurements appear less important. This result opens the way for future research to explore the consequences of adopting performance measures that are related to this high emphasis on the process.
Keywords: Measures; Process Measures; Agile Process; Agile Frameworks; Agile Practices; Customer focus